Methodological Appraisal of Literature Concerning the Analysis of Genetic Variants or Protein Levels of Complement Components on Susceptibility to Infection by Trypanosomatids: A Systematic Review - Tirado, Thais Cristina; Moura, Larine Lowry; Shigunov, Patrícia; Figueiredo, Fabiano Borges (Frontiers in Immunology, 2021)
Background: Trypanosomatids are protozoa responsible for a wide range of diseases, with emphasis on Chagas Disease (CD) and Leishmaniasis, which are in the list of most relevant Neglected Tropical Diseases (NTD) according to World Health Organization (WHO). During the infectious process, immune system is immediately activated, and parasites can invade nucleated cells through a broad diversity of receptors. The complement system − through classical, alternative and lectin pathways − plays a role in the first line of defense against these pathogens, acting in opsonization, phagocytosis and lysis of parasites. Genetic modifications in complement genes, such as Single Nucleotide Polymorphisms (SNPs), can influence host susceptibility to these parasites and modulate protein expression. Methods: In March and April 2021, a literature search was conducted at the PubMed and Google Scholar databases and the reference lists obtained were verified. After applying the inclusion and exclusion criteria, the selected studies were evaluated and scored according to eleven established criteria regarding their thematic approach and design, aiming at the good quality of publications. Results: Twelve papers were included in this systematic review: seven investigating CD and five focusing on Leishmaniasis. Most articles presented gene and protein approaches, careful determination of experimental groups, and adequate choice of experimental techniques, although several of them were not up-to-date. Ten studies explored the association of polymorphisms and haplotypes with disease progression, with emphasis on lectin complement pathway genes. Decreased and increased patient serum protein levels were associated with susceptibility to CD and Visceral Leishmaniasis, respectively. Conclusion: This systematic review shows the influence of genetic alterations in complement genes on the progression of several infectious diseases, with a focus on conditions caused by trypanosomatids, and contributes suggestions and evidence to improve experimental design in future research proposals.